Therapeutic Development in Targeting Protein-Protein Interactions With Synthetic Topological Mimetics - Tsou, Lun K. (2012)
Protein-protein interactions lie at the heart of cellular signaling pathways and the deregulation of which has frequently led to diseases. In contrast to inhibitors that bind to distinctive enzyme active sites, molecules targeting protein surface topologies have been underexploited in drug development. The challenges in developing protein surface antagonists or agonists originate from the relatively large and flat surface areas that lack well-defined cavities required for sufficient binding affinity. In the past decade, our understanding of protein recognition has served as solid basis for the design of synthetic mimetics to modulate these protein-protein interactions. Herein, we summarize recent successes in the development of synthetic α-helix mimetics, proteomimetics, and biologics with the therapeutic potentials of inhibiting tumourgenesis or cancer-related viral infections.